The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1080/19443994.2015.1076738
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, and photocatalytic activity of TiO2–SiO2nanocomposites

Abstract: Introduction of complex chemical compounds in the wastewater treatment plants challenged the biological process efficiency. Photocatalyst oxidation was newly introduced to remove the trace organic contaminations. Since their surface area determined the production of hydroxyl radicals, the pure TiO 2 surface area was increased by the preparation of TiO 2 -SiO 2 nanocomposite using sol-gel technique. Later on, the X-ray diffraction, scanning electron microscopy, energy diffraction spectroscopy, Fourier transform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…So that photocatalytic effects are restricted only for the ultraviolet region of the light spectrum. In recent years, numerous studies have shown that TiO 2 supported on SiO 2 exhibits an enhanced photocatalytic activity that makes TiO 2 /SiO 2 particularly attractive for catalytic application [12][13][14]. In this work, the modification at interfaces of TiO 2 /SiO 2 /Si structures after implantation as a function of energy and atomic mass of the implanted ions using RBS method will be presented.…”
Section: Introductionmentioning
confidence: 98%
“…So that photocatalytic effects are restricted only for the ultraviolet region of the light spectrum. In recent years, numerous studies have shown that TiO 2 supported on SiO 2 exhibits an enhanced photocatalytic activity that makes TiO 2 /SiO 2 particularly attractive for catalytic application [12][13][14]. In this work, the modification at interfaces of TiO 2 /SiO 2 /Si structures after implantation as a function of energy and atomic mass of the implanted ions using RBS method will be presented.…”
Section: Introductionmentioning
confidence: 98%
“…28 Among the various types of supporting metal oxides, SiO 2 has various advantages because it minimizes recombination, increases adsorption capacity, and prevents agglomeration. 29 Erdural et al (2014) added synthesized SiO 2 to TiO 2 photocatalyst with various concentrations, leading to inactivation ranging from 14.2 to 99.9% for E. coli bacteria. 30 SiO 2 is obtained through synthesis or extraction from natural materials, both biological and non-biological.…”
Section: Introductionmentioning
confidence: 99%
“…Jamal et al (2014) summarized the major threatening in producing a good PNCs mainly falls on choosing a relevant nanostructured semiconductor particle and its compatible nature with the polymer matrix. Ijadpanah-Saravi et al (2014) recommended the development of appropriate handling system to diffuse and disseminate the nanostructured semiconductor material inside the polymer matrix has become a main concern. The following cationic dyes like methylene blue (MB), bismarck brown (BB) & malachite green (MG) and anionic dyes like methyl orange (MO) and alizarin red S (ARS) are selected for the present research study using polyazomethine/ZnO (PNZ) and polyazomethine/TiO2 nanocomposites (PNT).…”
Section: Introductionmentioning
confidence: 99%